Ultrasound detection of lymphatic bubbles in a porcine dive model - Currens, Joshua B.; Moon, Richard E.; Makowski, Matthew S.; Natoli, Michael J.; Leypoldt, Jayne; Woolard, Jean; Brown, David; Azarang, Arian; Brown, Robert; Schinazi, Eric; Ransom, Zach; Papadopoulou, Virginie; et al. (Journal of applied physiology (1985), 2025)
This is the first ever study to noninvasively detect lymphatic decompression bubbles and examine their correspondence with severe decompression sickness (DCS) outcome. The image brightness analysis found that subjects with severe DCS were likely to have darker lymph node images postdive indicating potential gas presence, after variable ultrasound system settings were unified post hoc. These findings may provide an early framework for a wearable ultrasound device to monitor real-time decompression stress. Ultrasound is currently the optimal imaging modality in the decompression research field for assessing intracorporeal gas. Decompression sickness (DCS) is triggered by excess gas bubble presence in the body; however, the relationship is not well understood. Presently, the decompression physiology field does not have a strong predictive DCS biomarker. In this study, we explore the presence of lymph node decompression bubbles in a porcine model after a provocative hyperbaric exposure. Porcine test subjects ( n = 37 subjects) underwent an aggressive decompression profile as part of a larger study, and a subsequent investigation of the left inguinal lymph node was conducted with ultrasound. Ultrasound images were assessed by three trained sonographers for lymph node bubbles. Regional brightness was analyzed after post hoc phantom-calibrated standardization of ultrasound depth and gain settings. Out of the 37 animals that we examined for lymph node bubbles, 17 were diagnosed with severe DCS and 14 identified to have lymph node bubbles. A postmortem dissection was conducted for a few animals, and bubbles could be found streaming from the lymph node corresponding to a severe DCS subject. The brightness assessment of the standardized ultrasound images indicated that DCS cases typically had a decrease in the region intensity after the dive with a potential peak sensitivity of 94.1% and specificity of 55% based on receiver-operating curve analysis. This study is the first noninvasive detection of lymph node decompression bubbles with confirmation of bubbles by postmortem dissection. A positive correlation between lymph node bubbles and DCS severity was found. NEW & NOTEWORTHY This is the first ever study to noninvasively detect lymphatic decompression bubbles and examine their correspondence with severe decompression sickness (DCS) outcome. The image brightness analysis found that subjects with severe DCS were likely to have darker lymph node images postdive indicating potential gas presence, after variable ultrasound system settings were unified post hoc. These findings may provide an early framework for a wearable ultrasound device to monitor real-time decompression stress.